Class, affective labour and exploitation: Unemployment and the creation of work on the margins. Issue 1 (January 2021) - Gerrard, Jessica; Farrugia, David
This article examines the articulation of class and affective labour in the creation of work for the unemployed. Bringing together two sets of interlinking literature on work, class and subjectivity – the proliferating and increasingly popular literature on affective labour and the highly influential Bourdieusian inspired sociologies of class – we argue for closer research attention to the specificities of exploitation in contemporary experiences of paid employment. To do this, we draw on in-depth research on the informal work created by the social enterprise The Big Issue . This research demonstrates the ways in which affective labour is enacted through the productive exchange of commodities and the cultivation of particular worker dispositions. In the process, the homeless and long-term unemployed are positioned as productive workers and classed subjects through the disciplinary requirements of this form of affective labour.